Privatization and economic strategy in Mozambique - Carlos Castel-Branco; Christopher Cramer; Degol Hailu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
Privatization, together with liberalization and deregulation, constituted the core of Mozambique's economic transition. Privatization in Mozambique has taken place on an unusually large scale in comparison with the rest of Africa. Privatization interacted with military demobilization and political transition since military officers, together with members of the main political parties, were amongst the buyers of state assets. Private businessmen who had profited from the war economy also found a new outlet for their capital through privatization, sometimes in joint ventures with foreign investors. However, Mozambique's privatization programme was bedevilled by a lack of transparency. In some cases, traditional community claims—to land and natural resources—were ignored in the scramble to dispose of state farms. Privatization, like all reforms, involves a political process in which some people have more `voice' than others do— often by virtue of their wealth and political power.
Keywords: O10; O55; 330; sub-Saharan Africa; Mozambique; conflict; economic reform; Privatisierung; Wirtschaftsreform; Mosambik